조직원의 조화열정과 집중이 지각된 성과에 미치는 영향: 강점활용 집단별 차이비교를 중심으로 - 이혜숙; 김보영; Lee, Hae Sook; Kim, Bo-Young (한국콘텐츠학회 논문지, 16(12), 2016)
This research is to investigate the impact of strengths use and development on individual perceived performance. The present research aimed at exploring the role of harmonious passion and concentration on individual perceived performance and in this relation verify the group difference by the level of strengths use. This study was conducted on a sample of 460 employees and structural equation modelling analyses were performed to test the proposed model. The results showed that harmonious passion and concentration is positively related to individual perceived performance. In the relation between harmonious passion and perceived performance, there was the difference between high strength use group and low strength use group. Over all, the findings provide encouraging support for the potential benefits of employee's strengths use at work and the importance of intrinsic motivation variable on perceived performance. In addition practical implications on developing employee strengths use are discussed. 본 연구는 기업 내 조직원의 강점활용을 통한 조화열정과 집중이 지각된 성과에 미치는 영향을 실증적으로 규명하고자 했다. 이에 본 연구는 조직 내 구성원의 조화열정과 집중이 지각된 성과에 미치는 영향과 이 관계에서 강점 활용의 집단 별 차이를 비교 분석하는 연구 모형을 설계하고 국내 기업 내 조직구성원 총 460명을 대상으로 수집된 설문을 통해 분석하였다. 분석결과 조직원들의 조화열정과 집중은 지각된 성과에 긍정적인 영향을 미치는 것으로 나타났다. 특히 조화열정과 지각된 성과의 관계에서는 강점 활용 정도에 따른 고집단과 저집단을 비교했을 때 고집단에서만 유의미한 관계가 나타나는 것으로 확인되어 조화열정과 같은 조직원의 심리적 변인들을 성과로 연결시키는데 있어서 강점활용이 영향요인으로 작용할 수 있음을 확인할 수 있었다. 본 연구는 조직의 강점 활용이 개인과 조직에게 미치는 잠재적 유익을 실증적으로 제시했다는데 그 의의가 있으며, 조직 구성원들의 심리적 동기 변인과 강점활용의 중요성을 강조하고, 그 활용방안을 모색하고자 했다.